2021
DOI: 10.1038/s41598-021-84678-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of angiotensin-converting enzyme inhibitors and angiotensin-receptor blockers with risk of mortality, severity or SARS-CoV-2 test positivity in COVID-19 patients: meta-analysis

Abstract: The effects of angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin II receptor blockers (ARBs) in the treatment of COVID-19 are highly debated. This study was aimed to assess aggregated risk by investigating the association of ACEIs/ARBs users against non-users of ACEIs/ARBs with the risk of mortality or severe clinical manifestations or magnitude of SARS-CoV-2 test positivity in COVID-19 patients. Systematic literature search was carried out in different databases for eligible studies. The pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Despite aforementioned concerns regarding a potentially increased propensity for more severe disease by way of enhanced viral entry via upregulated ACE2 receptors in patients on RAAS pathway inhibitors, 47 accumulating retrospective and prospective data as well as a joint statement by the American College of Cardiology (ACC)/American Heart Association (AHA)/Heart Failure Society of America (HFSA) affirm that RAAS pathway inhibitors should generally not be discontinued in patients with HF who are at risk for or hospitalized with COVID-19. [56][57][58][59] In fact, discontinuation of these medications in patients not only with HF but also hypertension and coronary artery disease has not been shown to improve outcomes and likely deprives patients of evidence-based therapy. 57 Statins have been studied as treatment in COVID-19.…”
Section: Medical Managementmentioning
confidence: 99%
“…Despite aforementioned concerns regarding a potentially increased propensity for more severe disease by way of enhanced viral entry via upregulated ACE2 receptors in patients on RAAS pathway inhibitors, 47 accumulating retrospective and prospective data as well as a joint statement by the American College of Cardiology (ACC)/American Heart Association (AHA)/Heart Failure Society of America (HFSA) affirm that RAAS pathway inhibitors should generally not be discontinued in patients with HF who are at risk for or hospitalized with COVID-19. [56][57][58][59] In fact, discontinuation of these medications in patients not only with HF but also hypertension and coronary artery disease has not been shown to improve outcomes and likely deprives patients of evidence-based therapy. 57 Statins have been studied as treatment in COVID-19.…”
Section: Medical Managementmentioning
confidence: 99%
“…The use of ACEI/ARB inhibitors in COVID-19 illness has been the focus of multiple research studies since the start of the pandemic due to a theoretical concern that it may increase the expression of the ACE2 receptor, which is needed by the SARS CoV-2 virus for cell entry [ 23 , 24 ]. However, this has not been validated in subsequent studies [ 25 , 26 ]. In our study, the use of ACEI/ARB was associated with lower survival after CP therapy.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies have demonstrated that ACEI/ARB treatment in COVID-19 patients is associated with a reduced mortality risk, with a meta-analysis demonstrating a reduction in all-cause mortality [ 44 , 45 ]. Zhang et al [ 46 ] showed no significant difference in the outcome and length of hospital stay in hypertensive COVID-19 patients who continued to take RAS inhibitors compared to the control group [ 46 ]. Another study indicated that the peak viral load for patients taking ACEI/ARBs was significantly lower than the control group (p = 0.03), even though the baseline viral load remained the same for both groups [ 38 ].…”
Section: Targeting Covid-19 Therapymentioning
confidence: 99%